2016
DOI: 10.1186/s12909-016-0755-5
|View full text |Cite
|
Sign up to set email alerts
|

Proficiency in identifying, managing and communicating medical errors: feasibility and validity study assessing two core competencies

Abstract: Background: Communication skills and professionalism are two competencies in graduate medical education that are challenging to evaluate. We aimed to develop, test and validate a de novo instrument to evaluate these two competencies.Methods: Using an Objective Standardized Clinical Examination (OSCE) based on a medication error scenario, we developed an assessment instrument that focuses on distinctive domains [context of discussion, communication and detection of error, management of error, empathy, use of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…The InCoPrA was developed, reviewed, and pilot-tested previously, taking into consideration the ACGME definition of competencies and existing tools used for other OSCE scenarios and competencies evaluation [ 52 54 ] and the feedback provided during the pilot testing [ 24 ]. The InCoPrA constructs assess professionalism if the trainee; 1) demonstrates integrity and ethical behavior; 2) accepts responsibility and follows through on tasks; and 3) demonstrates empathic care for patients.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The InCoPrA was developed, reviewed, and pilot-tested previously, taking into consideration the ACGME definition of competencies and existing tools used for other OSCE scenarios and competencies evaluation [ 52 54 ] and the feedback provided during the pilot testing [ 24 ]. The InCoPrA constructs assess professionalism if the trainee; 1) demonstrates integrity and ethical behavior; 2) accepts responsibility and follows through on tasks; and 3) demonstrates empathic care for patients.…”
Section: Methodsmentioning
confidence: 99%
“…Building on our previous work [24], we have developed four scenarios which have been reviewed for content, realism, acceptability and expert validity by participating faculty members, leadership, SPs and non-participating learners. These scenarios were pertinent to: 1) detection of medical error [24,55,56]; 2) managing chronic opioid use; 3) Managing depression; and 4) Delivering bad news. In all these scenarios, the learners had access to a simulated EMR and EMIRs to help in identifying medical history, medication use, interactions and side effects.…”
Section: Simulation Scenariosmentioning
confidence: 99%
See 2 more Smart Citations
“…The same study found that the correlation between the mean real patient and SP scores was not strong (Spearman rank correlation=0.28) [7]. In another study, when both SPs and faculty were used to assess the communication skills and professionalism of resident physicians, the inter-rater agreement between faculty was substantial (Fleiss kappa=0.71), but the measured agreement between faculty and SPs was only fair (Fleiss kappa=0.36) [8]. …”
Section: Introductionmentioning
confidence: 99%